The Correlation between CMV Infection and Hypertension in Iraqi Patients - G. Al-Suhail, Raghad; L. Saadoon, Noor; F. Salloom, Dunya (Iraqi Journal of Science, 2023)
In order to study the correlation between CMV infection and increase in blood pressure among Iraqi patients, 201 blood samples were collected including; 88 male, 113 female hypertensive patients and 40 control samples. Patients sera were grouped into patients who are under medication (T), and patients who do not take any treat-ment for hypertension(NT). Samples were tested for CMV-IgM/IgG by ELISA, ren-in enzyme and interleukin-6(IL-6) levels were determined by ELISA too. The opti-cal density readings difference for CMV-IgG were significant between (T) and (NT) groups as well as when each group compared to control, level of renin enzyme showed significant difference between patients group(T and NT) and between each group compared to the control, (135 ± 98), (201 ± 102) and (130 ± 90) respectively, while IL-6 level was not significant either between the groups nor within the group. Furthermore, there was a positive correlation between the optical density readings of (NT) group for CMV-IgG and renin enzyme level with the systolic and diastolic blood pressure with r-value ranged (0.4-0.6). This study may high light on the role of previous infection or re-infection by CMV and increase in blood pressure.